2020
DOI: 10.1002/pmrj.12376
|View full text |Cite
|
Sign up to set email alerts
|

Falls After Dysvascular Transtibial Amputation: A Secondary Analysis of Falling Characteristics and Reduced Physical Performance

Abstract: Introduction Over half of all people with lower limb amputation (LLA) experience at least one fall annually. Furthermore, the majority of LLAs result from dysvascular health complications, contributing to balance deficits. However, fall‐related research specific to dysvascular LLA remains limited. Objective To characterize falls among adults with dysvascular LLA, using an existing Fall‐Type Classification Framework and to describe the functional characteristics of participants across the framework categories. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 61 publications
(163 reference statements)
1
30
0
Order By: Relevance
“…Not all falls caused injury; and not all injuries were caused by falls. Falls occurred both indoors and outdoors, but most falls occurred indoors consistent with research that found more falls occurred in the home than in community ( Anderson et al, 2021 ). The results suggest that PLL are exposed to falls whether or not they access the outdoor settings that present attentional and cognitive challenges identified as risks for falls ( Coffey et al, 2012 ).…”
Section: Discussionsupporting
confidence: 81%
“…Not all falls caused injury; and not all injuries were caused by falls. Falls occurred both indoors and outdoors, but most falls occurred indoors consistent with research that found more falls occurred in the home than in community ( Anderson et al, 2021 ). The results suggest that PLL are exposed to falls whether or not they access the outdoor settings that present attentional and cognitive challenges identified as risks for falls ( Coffey et al, 2012 ).…”
Section: Discussionsupporting
confidence: 81%
“…ActiGraph (ActiGraph, Pensacola, USA) [29,31,32,39,41,43,45,47,53,70,75,[80][81][82][83]92,105,109], FitBit (FitBit, San Francisco, USA) [34,40,52,76,108,117], and activPAL (PAL Technologies, Glasgow, Scotland) [26,36,37,68,91,103,104].…”
Section: Inclusion Of Sources Of Evidencementioning
confidence: 99%
“…The most frequently used wearable technologies were the StepWatch (Modus Health, Edmonds, Santa Monica, CA, USA) [4,21,25,27,28,30,42,44,46,[48][49][50][51]54,57,58,61,64,65,69,73,[77][78][79]84,[86][87][88][89][90][94][95][96]98,100,101,110,[114][115][116], ActiGraph (ActiGraph, Pensacola, FL, USA) [29,31,32,39,41,43,45,47,53,70,...…”
Section: Inclusion Of Sources Of Evidencementioning
confidence: 99%
See 2 more Smart Citations